2018
DOI: 10.1080/10641963.2018.1441859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestational diabetes mellitus on time to delivery and pregnancy outcomes in full-term pregnancies with dinoprostone labor induction

Abstract: GDM did not affect the time to delivery, cesarean delivery and other perinatal outcomes in Chinese women underwent dinoprostone-induced labor. However, it may be associated with the lower rates of delivery within different time intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In patients without contractions, we found that the rate of vaginal delivery was increased significantly at 39–39 + 6 gestational weeks when given iatrogenic intervention, but there were no differences in the vaginal delivery rate at 40–40 + 6 gestational weeks. This is the same with a study involving Chinese pregnant women on induction of labor with dinoprostone in a patient with GDM [ 25 ]. Therefore, we recommend that iatrogenic intervention be performed at 39–39 + 6 weeks of gestation to induce labor.…”
Section: Discussionsupporting
confidence: 76%
“…In patients without contractions, we found that the rate of vaginal delivery was increased significantly at 39–39 + 6 gestational weeks when given iatrogenic intervention, but there were no differences in the vaginal delivery rate at 40–40 + 6 gestational weeks. This is the same with a study involving Chinese pregnant women on induction of labor with dinoprostone in a patient with GDM [ 25 ]. Therefore, we recommend that iatrogenic intervention be performed at 39–39 + 6 weeks of gestation to induce labor.…”
Section: Discussionsupporting
confidence: 76%
“…In 2017, the obstetricians in Hubei Province of China had evaluated the use of Dinoprostone, and revealed that the vaginal delivery rate of those using Dinoprostone was higher than that of the entire year. It was safe to use Dinoprostone in Chinese population, even in some subgroups of patients with gestational diabetes mellitus (GDM) or hypertension (18,19). The effectiveness and safety of Dinoprostone and doubleballoon catheter stratified by Bishop score were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Feleke et alalso showed the association of GDM with a history of abortion, and reported that abortion increases the risk of GDM in the future pregnancies. In his study, the chances of GDM in women with a history of abortion were 5 times higher [ 32 ], which may be due to the effect of abortion on impaired normal insulin metabolism in women [ 33 ].…”
Section: Discussionmentioning
confidence: 99%